Narrow Gap flux-cored arc welding of high strength shipbuilding steels - Keltanen, Juha-Pekka (2015)
This thesis is part of the Arctic Materials Technologies Development –project. The research of the thesis was done in cooperation with Arctech Helsinki Shipyard, Lappeenranta University of Technology and Kemppi Oy. Focus of the thesis was to study narrow gap flux-cored arc welding of two high strength steels with three different groove angles of 20°, 10° and 5°. Welding of the 25 mm thick E500 TMCP and 10 mm thick EH36 steels was mechanized and Kemppi WisePenetration and WiseFusion processes were tested with E500 TMCP steel. EH36 steel test pieces were welded without Wise processes. Shielding gases chosen were carbon dioxide and a mixture of argon and carbon dioxide. Welds were tested with non-destructive and destructive testing methods. Radiographic, visual, magnetic particle and liquid penetrant testing proved that welds were free from imperfections. After non-destructive testing, welds were tested with various destructive testing methods. Impact strength, bending, tensile strength and hardess tests proved that mechanized welding and Wise processes produced quality welds with narrower gap. More inconsistent results were achieved with test pieces welded without Wise processes. Impact test results of E500 TMCP exceeded the 50 J limit on weld, set by Russian Maritime Register of Shipping. EH36 impact test results were much closer to the limiting values of 34 J on weld and 47 on HAZ. Hardness values of all test specimens were below the limiting values. Bend testing and tensile testing results fulfilled the the Register requirements. No cracking or failing occurred on bend test specimens and tensile test results exceeded the Register limits of 610 MPa for E500 TMCP and 490 MPa for EH36. Tämä työ on osa Arctic Materials Technologies Development -projektia. Diplomityö tehtiin yhteistyössä Arctech Helsingin telakan, Lappeenrannan teknillisen yliopiston ja Kemppi Oy:n kanssa. Työn tavoitteena oli tutkia lujien terästen mekanisoitua MAG-täytelankakapearailohitsausta. Kahdesta eri lujuusluokan ja paksuuden teräksistä ...